Dysautonomia following Lyme disease: a key component of post-treatment Lyme disease syndrome? - Adler, Brittany L.; Chung, Tae; Rowe, Peter C.; Aucott, John (Frontiers in Neurology, 2024)
Dysautonomia, or dysfunction of the autonomic nervous system (ANS), may occur following an infectious insult and can result in a variety of debilitating, widespread, and often poorly recognized symptoms. Dysautonomia is now widely accepted as a complication of COVID-19 and is an important component of Post-Acute Sequelae of COVID-19 (PASC or long COVID). PASC shares many overlapping clinical features with other infection-associated chronic illnesses including Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) and Post-Treatment Lyme Disease Syndrome (PTLDS), suggesting that they may share common underlying mechanisms including autonomic dysfunction. Despite the recognition of this complication of Lyme disease in the care of patients with PTLD, there has been a scarcity of research in this field and dysautonomia has not yet been established as a complication of Lyme disease in the medical literature. In this review, we discuss the evidence implicating B. burgdorferi as a cause of dysautonomia and the related symptoms, propose potential pathogenic mechanisms given our knowledge of Lyme disease and mechanisms of PASC and ME/CFS, and discuss the diagnostic evaluation and treatments of dysautonomia. We also outline gaps in the literature and priorities for future research.